Do future biology teachers bug out with higher insect-related knowledge and more positive attitudes? A comparison of different education levels - Roxanne Gutowski; Petr Novotný; Vanda Janštová; Jörg Großschedl (Frontiers in Education)
IntroductionGlobal species extinction rates are increasing, with a particularly severe impact on insects. Biology teachers are crucial in raising students’ awareness of insects’ importance for the economy (e.g., food production) and ecosystems. Consequently, it is essential for biology teachers to possess comprehensive knowledge about insects and to maintain a positive attitude toward them.MethodsTherefore, our cross-sectional study examines the knowledge and attitudes of students across five educational levels with a particular focus on pre-service teachers: levels 1 to 3 represent secondary school students (n = 362) at different stages, while levels 4 and 5 represent pre-service biology teachers (n = 212) in the bachelor’s and master’s programs.Results and discussionOur results show a moderate to strong positive correlation between knowledge and attitudes across all education levels. Participants with a higher educational level have more knowledge on average. Participants in levels 1, 4, and 5 have more positive attitudes than those in levels 2 and 3. No gender differences were observed regarding knowledge but regarding attitudes, with males showing a more positive attitude.ConclusionResults indicate that pre-service biology teachers are well prepared, showing good insect-related knowledge and relatively positive attitudes.